Pain and disability following fusion for idiopathic adolescent scoliosis: prevalence and associated factors - Bas, Teresa; Franco, Nuria; Bas, Paloma; Bas, Jose Luis (Evidence-Based Spine-Care Journal, 2012)
Study design: Retrospective prognostic study.Objectives: To describe the prevalence of pain following fusion for adolescent idiopathic scoliosis and to identify factors associated with pain and disability.Methods: From 126 consecutive patients surgically treated for scoliosis between 1997 and 2007, 104 (82.5%) completed SRS-22 and ODI questionnaires at a last follow-up (mean, 4.8 years; range 1–11.2 years). Prevalence of pain and disability were determined from SRS questions 1 and 9 respectively, with “any” pain or decrease in activity considered clinically significant. SRS Pain Domain Scores (PDS) were also evaluated.Results: Most participants reported “no pain” (38.5%) or “mild pain” (30.8%) and 72.1% of participants reported a current work/school activity level of 100% normal. An association between instrument type and the presence of any pain in the previous 6 months was noted (P = .022). Instrument type was the only factor that was significantly associated with the PDS (P = .0052).Conclusions: The high percentage of patients reporting no pain or mild pain may suggest overall success of the procedures. Although an association between instrument type and pain was seen, unmeasured factors that contributed to the decision of what instrument to use may confound the relationship. From these data a causal inference cannot be made.